Outcome of Obstructed Labour in Kano, Nigeria - Omole-Ohonsi, Abiodun; Belga, Francis (Nepal Journal of Obstetrics and Gynaecology, 2011)
DOI: http://dx.doi.org/10.3126/njog.v5i2.5077 NJOG 2010 Nov-Dec; 5(2): 38-42